Technology Acceptance Model and Risk Benefit Perception on Food Online Purchase in SMEs - Kurnia Hardi; Burhan; Muhammad Ridhwan (LP2M IAIN Palopo, 2025)
The disruption of information technology has increasingly influenced how consumers transact. This research aims to examine the impact of technology acceptance levels and perceived risk-benefit on food product purchases in SMEs through online transactions. The survey was conducted with respondents by distributing questionnaires in the Jabodetabek area, with 200 questionnaires collected for further processing. The analysis method used is SEM-PLS. The results indicate indirect effect of technology acceptance and perceived benefits on food product purchases in SMEs through the adoption of online transactions. The direct effect of perceived benefits of digital technology on food product purchases in SMEs shows that the adoption of online transactions has a partially complementary mediating effect. Consumers are partially adopting alternatives such as social media applications for actual purchases, in line with the fact that most SMEs have yet to go digital. This research recommends that the government and relevant institutions enhance the acceleration of digitalization in SMEs through training and mentoring programs. SME players need to focus on efficient business strategies by shifting resources to more essential types of businesses and improving digital literacy while adopting online transactions for business expansion.